2022
DOI: 10.1038/s41419-022-05109-9
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid control of ciliogenesis modulates insulin signaling in hypothalamic neurons through an autophagy-dependent mechanism

Abstract: Palmitic acid (PA) is significantly increased in the hypothalamus of mice, when fed chronically with a high-fat diet (HFD). PA impairs insulin signaling in hypothalamic neurons, by a mechanism dependent on autophagy, a process of lysosomal-mediated degradation of cytoplasmic material. In addition, previous work shows a crosstalk between autophagy and the primary cilium (hereafter cilium), an antenna-like structure on the cell surface that acts as a signaling platform for the cell. Ciliopathies, human diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…These findings were consistent with another study [ 23 ] in which EA plus BC2000 intervention significantly regulated autophagy and mitophagy pathways. Autophagy can play an important role in various physiological and pathological processes such as cell homeostasis, ageing, immunity, tumorigenes, and neurodegenerative diseases [ 24 ]. Studies have shown that urolithin A, a metabolite of EA in the gut, can prolong the lifespan of nematodes and improve muscle function in rodents by inducing autophagy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with another study [ 23 ] in which EA plus BC2000 intervention significantly regulated autophagy and mitophagy pathways. Autophagy can play an important role in various physiological and pathological processes such as cell homeostasis, ageing, immunity, tumorigenes, and neurodegenerative diseases [ 24 ]. Studies have shown that urolithin A, a metabolite of EA in the gut, can prolong the lifespan of nematodes and improve muscle function in rodents by inducing autophagy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 In addition, the loss of cilia and autophagy in the POMC neurons can disrupt insulin signaling, prevent insulin-dependent glucose uptake, and eventually lead to obesity and insulin resistance in mice. 45 Recently, novel molecules and mechanisms related to insulin resistance have gradually been revealed. For instance, inositolrequiring enzyme 1α (IRE1α), 46 spliced X-box binding protein 1 (XBP1s), 47 and other positive regulatory factors can activate the POMC neurons, enhance peripheral insulin sensitivity, improve glucose tolerance, inhibit liver glucose production, and thus, prevent obesity and type 2 diabetes.…”
Section: Insulin and Its Receptormentioning
confidence: 99%
“…Moreover, compensatory secretion of insulin leads to hyperinsulinemia, which can lead to type 2 diabetes and obesity. In recent years, studies have found that some central factors are associated with insulin resistance, such as obesity, 42 hypothalamic inflammation, 43 endoplasmic reticulum stress, 44 and the cilia and autophagy mechanism, 45 which can prevent insulin from transmitting peripheral metabolic information to the center, resulting in impaired glucose metabolism. A long-term high-fat diet (HFD) or hypothalamic inflammation can activate some inflammatory factors such as toll-like receptor-4 (TLR4), tumor necrosis factor (TNF), myeloid differentiation factor 88 (MyD88), and nuclear factor-kappa B (NF-κB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many signaling pathways emanate from the primary cilium and among these, several are engaged in the regulation of metabolism ( Pala et al, 2017 ; Anvarian et al, 2019 ; Avalos et al, 2022 ; Yang et al, 2022a ). For example, an interplay between the Hedgehog and mTORC1 pathways exist ( Larsen and Moller, 2020 ), and both are regulated by the primary cilium.…”
Section: Introductionmentioning
confidence: 99%